Processing and characterization of ultra-high temperature oxide fiber-reinforced oxide ceramic matrix composites with improved thermomechanical properties - Kaya, Cengiz; Kaya, Figen (TRANS TECH PUBLICATIONS LTD, 2008)
A combined technique comprising electrophoretic deposition (EPD) and low-pressure infiltration was used for the fabrication of multi-layer woven mullite ceramic fabric reinforced alumina ceramic matrix composites (CMCs) for high temperature applications. Two different interface materials, NdPO4 and ZrO2 were synthesised and used for coating the woven ceramic fibres by EPD. The manufactured CMC components with suitable interface material are targeted for use at 1300-1400 degrees C in an oxidising atmosphere and have shown very good mechanical properties in multi-layer plate forms. Damage mechanisms, such as debonding, fibre fracture, delamination and matrix cracking within the composite plates subjected to flexural loading are analysed. It is shown that the composites with NdPO4 interface and 40 vol.% fibre loading have better mechanical properties in terms of strength and damage-tolerant behaviour. The final components produced are considered to be suitable for use as shroud seals and insulating layers for combustor chambers in aircraft engines.
Keywords: alumina; mullite fibres; interphase; electrophoretic deposition; Materials Science